The Principle of Equality Before the Law for Rape Victims of Persons with Dual Sensory Disabilities in Criminal Law Perspective - Yedi Rizki Anugrah (Riviera Publishing, 2025)
The principle of equality before the law is fundamental to ensuring justice in any legal system. In Indonesia, however, individuals with dual sensory disabilities, particularly those who are victims of sexual violence, often face discrimination and unequal treatment within the judicial process. This study explores the application of this principle in cases involving rape victims with dual sensory disabilities, addressing how these individuals often encounter challenges in accessing justice due to their communication difficulties. The research uses a normative juridical approach, reviewing existing legal frameworks, including Law Number 8 of 2016 on Persons with Disabilities, and relevant international conventions. Through literature study and case analysis, this research finds that while Indonesia’s legal framework provides for equal treatment under the law, persons with dual sensory disabilities still face barriers such as inadequate legal accommodations and discriminatory practices by law enforcement. The study highlights the need for comprehensive reforms, including better training for law enforcement and the provision of specific accommodations for individuals with sensory impairments. The implications of this research are crucial for ensuring that rape victims with dual sensory disabilities receive the same legal protections as any other individual, fostering a more inclusive legal system that guarantees equal rights for all citizens.